A Case of Polycystic Ovarian Disease Improved by Lycopodium (Advancements in Homeopathic Research, 2022)
A 22-year-old unmarried girl MissVTwas registeredin the PCOD project of Ayush (Ref. no. 73/ Enroll. no. 24)on 20/12/15 for treatment of irregular menses with phases of amenorrhoea and dysmenorrhoea for the last 6 years i.e. 1 year after menarche (LMP-15/12/ 15) with tendency to gain weight (Wt.: 75 kg). She also had falling of hair since 2-3 months and acne on face since 6 months. On investigations, she was confirmed to be a case of PCOD.
Keywords: PCOD; Polycystic Ovarian Disease; Lycopodium